30, 000 Years of the southwestern Lake Urmia (Iran) paleoenvironmental evolution inferred from mineralogical indicators from lake and watershed sediments. (November 2022) - Kong, Ting; Tudryn, Alina; Gibert-Brunet, Elisabeth; Tucholka, Piotr; Motavalli-Anbaran, Seyed-Hani; Ahmady-Birgani, Hesam; Lankarani, Mohammad; Miska, Serge; Noret, Aurélie; Dufaure, Olivier
Graphical abstract: Highlights: A robust chronology of sediments that matches the paleoclimate records from Lake Urmia (Iran) was established. Continuous lake evolution was recorded based on grain size and XRD mineralogical analyses that include total sediment and specific clay and carbonate fractions of the catchment and lake sediments for the last 30 kyr. Multi-proxy reconstructions suggest a humid Late Pleistocene, followed by frequent drier/wetter episodes, wet early Holocene and evaporative conditions during the Mid to Late Holocene transition. A tentative reconstruction of lake levels from selected lakes surrounding Lake Urmia was performed at the regional Middle East scale. Abstract: In order to understand the pattern and trends of the environmental evolution of Lake Urmia (Iran), one of the largest terminal lakes in Western Asia before its level drop over the past two decades, two sediment cores (Golman 6, 8.0 m; Golman 7, 12.5 m) were collected from the recently dried-out southwestern part of the lake. These sediment cores represent a continuous sedimentary sequence, composite core, that was extensively studied for grain size, total mineralogy including clay minerals, carbonates and their crystallinities, in comparison with the basin geological formations and within a reliable AMS- 14 C timescale. Lake Urmia deposits cover the time-span from 30 to ca 2 cal kyr BP. Grain-size of the siliclastic fractions from the lower part of the composite core consists of fine-silt and clay particles likely representing lacustrine deposits while the top sediments are characterized by variable composition of sand and silt. At about 30 cal kyr BP, our proxies indicate a low lake stand and even drying out at the coring site, which was followed by water level rise and the establishment of lacustrine conditions between 29.9 and 20.2 cal kyr BP. Since then, all our data suggest lake's highly unstable conditions. Subsequently, clearly low lake levels to sometimes the drying out was recorded during the 20.2–15.3 cal kyr BP, 13.3–11.8 cal kyr BP and 5.6–4.1 cal kyr BP intervals. In contrast, lacustrine conditions were re-established between 15.3 and 13.3 cal kyr BP, between 11.8 and 5.6 cal kyr BP and between 4 0.1 and 2.3 cal kyr BP. High water level recorded between 15.3 and 13.3 cal kyr BP can be attributed to the Bölling/Alleröd warming, and the following regressive phase during the 13.3–11.8 cal kyr BP period corresponds to the Younger Dryas period. In the Early-Mid Holocene, the lacustrine environment from 11.8 to 5.6 cal kyr BP was characterized by high aragonite and salt contents, highlighting evaporative environment as like during the 29.9–20.2 cal kyr BP period. Our results allowed the Late Quaternary climate reconstruction at Lake Urmia basin scale and record the past climate change at a larger Western Asia scale.